A concrete sealing and curing agent and preparation method thereof

By using β-cyclodextrin to wrap the concrete sealing and curing agents with components such as lithium silicate and isobutyltriethoxysilane emulsion, the problem of insufficient penetration depth and stability in the prior art is solved, and efficient concrete compaction is achieved The properties and waterproof and corrosion-resistant effect extend the service life of concrete.

CN118108477BActive Publication Date: 2025-02-25TAIAN RUINING BUILDING MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410290464.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-14
Publication Date
2025-02-25
Estimated Expiration
2044-03-14

AI Technical Summary

Technical Problem

The existing concrete sealing curing agent has shortcomings in terms of penetration depth and stability, and cannot effectively solve the problem of concrete durability.

Method used

β-cyclodextrin is used to encapsulate lithium silicate to form a lithium silicate composite, and isobutyl triethoxysilane is made into an emulsion, combining penetrant and Tween 80 to form a new concrete sealing curing agent. The curing agent can quickly penetrate into the concrete, react with free calcium to form insoluble amorphous hydrated calcium silicate, blocking capillary pores and tiny cracks, and at the same time forming a dense hydrophobic layer on the surface, improving waterproof and corrosion resistance.

Benefits of technology

The high permeability and stability of concrete sealing curing agent is achieved, the compactness, hardness, waterproofing and corrosion resistance of concrete is significantly improved, and the service life of concrete is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention belongs to the technical field of building materials, and specifically relates to a concrete sealing and curing agent and a preparation method thereof. The concrete sealing and curing agent provided by the present invention is mainly composed of a lithium silicate complex, an isobutyltriethoxysilane emulsion, a penetrant, Tween 80 and deionized water. The concrete sealing and curing agent prepared by the present invention has the advantages of high stability and strong permeability, can penetrate into the interior of the concrete well, react with free calcium to generate insoluble amorphous hydrated calcium silicate, and seal the capillary pores of the concrete, thereby improving the compactness and hardness of the concrete. At the same time, the concrete sealing and curing agent also has excellent waterproof and anti-corrosion properties, can effectively improve the water permeability, chloride ion permeability and carbonization resistance of the concrete, and can significantly extend the service life of the concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to a concrete sealing and curing agent and a preparation method thereof. Background Art

[0002] Concrete is a building material, which is mainly composed of raw materials such as cement, aggregate, fly ash, slag powder, etc. Concrete is widely used in infrastructure such as houses, roads and bridges because of its abundant sources and low prices. However, during the hardening process of concrete, its surface and internal structure contain a large number of interpenetrating pores and tiny cracks. When the concrete material encounters moisture or is in a humid environment for a long time, water will penetrate into the concrete through the pores or cracks, causing steel corrosion, destroying the internal structure of the building, and seriously affecting the durability of the concrete. At present, the main means to address the durability problem of concrete is to apply external protection to the concrete to slow down the deterioration of the concrete and improve the durability of the concrete.

[0003] Patent document CN102815885A discloses an improved liquid concrete sealing and curing agent, which includes a silicate, a penetrant, a surfactant, a surface modifier, a brightener and water, and the silicate is potassium silicate. The obtained liquid concrete sealing and curing agent has high strength, strong permeability, no shrinkage of the product, and corrosion resistance, which can improve the overall performance of the concrete surface. However, although the potassium silicate in the sealing and curing agent can improve the strength and wear resistance of concrete, it has poor durability and is prone to alkali reversion, which not only affects the beauty and service life of concrete, but also may cause rust or damage to the steel bars inside the concrete.

[0004] Patent document CN104150954A discloses a concrete sealing curing agent, which includes a silicate, a silane coupling agent, nano titanium dioxide and water; the silicate is sodium silicate, potassium silicate or lithium silicate, and the silane coupling agent is isobutyl triethoxysilane. After the sealing curing agent is applied to the surface of the concrete structure, the silicate component can quickly penetrate into the concrete and react with free calcium to generate insoluble amorphous hydrated calcium silicate, thereby achieving the blocking of the pores of the concrete structure and improving the hardness of the concrete structure. At the same time, the silane coupling agent and nano titanium dioxide in the curing agent can form a hydrophobic film layer on the surface of the concrete structure through synergistic action, increasing the hydrophobicity of the surface of the concrete structure. However, the isobutyl triethoxysilane in the sealing curing agent is prone to hydrolysis reaction when it encounters water. When isobutyl triethoxysilane comes into contact with water, the ethoxy group will be replaced by water molecules to generate isobutyl trihydroxy silane and release ethanol, which seriously affects the stability of the sealing curing agent.

[0005] Patent document CN113185184A discloses a concrete curing agent and its construction process, wherein the concrete curing agent comprises lithium silicate, methyl silicate, water reducing agent, coupling agent, micro-expansion agent, nano silica sol, single-component nano ceramic resin and distilled water. After the curing agent is mixed with concrete raw materials, the silicate and micro-expansion agent components can quickly penetrate into the concrete and react with free calcium to generate insoluble amorphous hydrated calcium silicate, thereby achieving the blocking of the pores of the concrete structure and improving the hardness and density of the concrete; at the same time, the ceramic material formed after the demulsification of the nano silica sol and the single-component nano ceramic resin can withstand the erosion of various corrosive media such as acid, alkali, salt, chloride ion, etc., preventing the cement concrete from corroding and carbonizing, thereby improving the corrosion resistance of the concrete. However, the hydrophobic layer formed by the reaction of the methyl silicate in the curing agent with carbon dioxide is relatively slow, and it takes a long time to achieve a reliable curing effect. Once rainy weather occurs, the unreacted or incompletely reacted methyl silicate will easily fall off the surface of the substrate, weakening the hydrophobic effect. In addition, the reaction products of the methyl silicate and the cement substrate contain some alkali metal carbonates, which will form obvious precipitates on the surface of the substrate. In severe cases, yellowing will occur, affecting the appearance of the substrate. Summary of the invention

[0006] In order to solve the defects of concrete sealing and curing agents in the prior art, the purpose of the present invention is to provide a concrete sealing and curing agent and a preparation method thereof. The concrete sealing and curing agent provided by the present invention is mainly composed of lithium silicate complex and isobutyl triethoxy silane emulsion. When the sealing and curing agent is coated on the surface of a concrete substrate, the lithium silicate complex in the curing agent can quickly penetrate into the concrete, react with the free calcium in the concrete, and generate insoluble amorphous hydrated calcium silicate, thereby achieving the sealing of concrete capillary pores or tiny cracks, improving the compactness and hardness of the concrete, and the isobutyl triethoxy silane emulsion in the curing agent can quickly form a dense hydrophobic layer inside and on the surface of the concrete, thereby improving the waterproof and corrosion resistance of the concrete. The sealing and curing agent provided by the present invention has the advantages of rapid response, strong permeability and high stability, and is a relatively ideal concrete sealing and curing agent.

[0007] The present invention provides a concrete sealing and curing agent, comprising the following components and their weight proportions:

[0008] 20-30 parts of lithium silicate complex, 10-18 parts of isobutyl triethoxy silane emulsion, 1-3 parts of penetrant, 1-2 parts of Tween 80 and 35-45 parts of deionized water.

[0009] Furthermore, the concrete sealing and curing agent is composed of the following components and their weight parts:

[0010] 26 parts of lithium silicate complex, 14 parts of isobutyltriethoxysilane emulsion, 2 parts of penetrant, 2 parts of Tween 80 and 40 parts of deionized water.

[0011] Furthermore, the preparation method of the lithium silicate composite is:

[0012] a. Add β-cyclodextrin to deionized water, heat to 65~70℃ and stir to dissolve, to obtain a saturated β-cyclodextrin aqueous solution;

[0013] b. Add lithium silicate to deionized water and stir evenly, the volume ratio of lithium silicate to deionized water is 1:1 to obtain a lithium silicate solution;

[0014] c. Slowly add the lithium silicate solution obtained in step b to the saturated β-cyclodextrin aqueous solution obtained in step a, stir the reaction in a constant temperature water bath, cool to room temperature, place at 4°C for 12 to 24 hours, filter, wash with water, and dry at 50 to 55°C for 8 to 10 hours to obtain.

[0015] Furthermore, the volume ratio of the lithium silicate solution to the saturated β-cyclodextrin aqueous solution in step c is 1:(2-3).

[0016] Furthermore, the temperature of the constant temperature water bath in step c is 45-55° C., and the reaction time is 3-4 hours.

[0017] Furthermore, the preparation method of the isobutyltriethoxysilane emulsion is:

[0018] A. Add β-cyclodextrin to deionized water, heat to 65-70°C and stir to dissolve, to obtain a saturated β-cyclodextrin aqueous solution;

[0019] B. Place Span 80 and isobutyltriethoxysilane in a homogenizer and stir evenly to obtain an oil phase;

[0020] C. Heat the saturated β-cyclodextrin aqueous solution obtained in step A to 40-45° C., then add the oil phase obtained in step B, stir at a constant temperature for 3-4 hours, and allow to cool.

[0021] Furthermore, in step B, the volume ratio of Span 80 to isobutyltriethoxysilane is 3:1.

[0022] Furthermore, the volume ratio of the oil phase to the β-cyclodextrin aqueous solution is 1:2.

[0023] Furthermore, the penetrant is polyethylene oxide with a molecular weight of 3000-5000.

[0024] In addition, the present invention also provides a method for preparing the concrete sealing and curing agent, comprising the following steps:

[0025] First, add the penetrant and Tween 80 into deionized water and stir evenly, then add the lithium silicate complex and isobutyl triethoxy silane emulsion and stir evenly to obtain the product.

[0026] The capillaries and tiny cracks inside the concrete are the main reasons that affect the hardness of the concrete, while the destruction and deterioration of the internal structure of the concrete are mainly related to moisture or the migration of moisture. Therefore, in order to improve the durability of concrete, it is necessary to improve the compactness and waterproof performance of the concrete. At present, the existing technology generally uses concrete sealing and curing agents for coating to achieve the effect of improving the hardness and waterproofing of the concrete. However, the existing sealing and curing agents generally have a problem of penetration depth, which leads to limited protective effect of the curing agent on the concrete and cannot completely solve the durability problem of the concrete.

[0027] In order to solve the above problems, the inventors consulted a large number of literature and materials, and conducted a large number of penetrant exploratory tests. The inventors found that the penetrant in the curing agent has a very limited penetration effect on the curing agent, and cannot solve the problem of the penetration depth of the curing agent. In the continuous in-depth research, the inventor team finally found a method to solve the penetration depth of the concrete sealing curing agent. The inventor unexpectedly discovered through experiments that the lithium silicate is formed by encapsulating lithium silicate with β-cyclodextrin. Compared with lithium silicate, the lithium silicate complex can penetrate into the concrete faster and better, and can better improve the compactness of the concrete. At the same time, the use of β-cyclodextrin to make isobutyl triethoxy silane into an emulsion can not only solve the problem of isobutyl triethoxy silane hydrolysis in water, but also effectively improve the stability of isobutyl triethoxy silane, so that the formed hydrophobic film can not only ensure the good breathing performance of the concrete, but also well inhibit the intrusion of water, and achieve excellent waterproof and anti-corrosion effects.

[0028] The concrete curing agent provided by the inventor has the characteristics of strong permeability and excellent waterproof and anti-corrosion effects. The specific principle of the sealing curing agent is as follows: the present invention uses β-cyclodextrin to wrap lithium silicate to form a lithium silicate complex. The β-cyclodextrin can promote the permeability of lithium silicate to concrete, and at the same time, it can prevent the lithium silicate that penetrates into the concrete from immediately reacting with the free calcium substances in the concrete, blocking the capillary pores on the surface of the concrete, and blocking the curing agent from continuing to penetrate, which can improve the permeation effect of the curing agent on the concrete. When the lithium silicate complex in the curing agent is completely penetrated, the β-cyclodextrin in the outer layer of the lithium silicate complex reacts with the strong calcium oxide in the concrete to form a complex, which preliminarily blocks the capillary pores of the concrete, and the released lithium silicate reacts with the free calcium substances in the concrete to generate insoluble amorphous hydrated calcium silicate to further block the capillary pores or tiny cracks of the concrete, which can greatly improve the compactness of the concrete.

[0029] Furthermore, the inventor uses β-cyclodextrin to make isobutyltriethoxysilane into an emulsion, which solves the problem of unstable hydrolysis of isobutyltriethoxysilane in water, can use water as a solvent, avoids the use of organic solvents as carriers, and improves the environmental protection of the curing agent. When the isobutyltriethoxysilane emulsion provided by the present invention penetrates into the interior of the concrete, the encapsulated β-cyclodextrin reacts with the strong calcium oxide in the concrete to form a complex, which can further block the capillary pores of the concrete and reduce the amount of lithium silicate used. At the same time, the isobutyltriethoxysilane emulsion can form a dense protective film on the surface of the concrete and deep into the inner wall of the capillary pores, inhibit the penetration of moisture and the transfer of free water inside the concrete, ensure the drying of the concrete surface and the interior, and can significantly improve the waterproof and anti-corrosion properties of the concrete. In addition, the protective film will not affect the air permeability of the concrete, can maintain the good breathability of the concrete, and can effectively extend the service life of the concrete.

[0030] Furthermore, the polyethylene oxide with a molecular weight of 3000-5000 provided by the present invention can further improve the penetration effect of the curing agent, and using Tween 80 as a surfactant can more effectively maintain the stability of the sealing curing agent, so that the prepared sealing curing agent has the characteristics of strong permeability, excellent waterproof and anti-corrosion effects, and can well solve the durability problem of concrete.

[0031] Compared with the prior art, the concrete sealing and curing agent provided by the present invention has the following advantages:

[0032] (1) The concrete sealing and curing agent provided by the present invention has the advantages of high stability and strong permeability, and can penetrate into the interior of the concrete well, react with free calcium to generate insoluble amorphous calcium silicate hydrate, and block the capillary pores of the concrete, thereby improving the density and hardness of the concrete;

[0033] (2) The concrete sealing and curing agent provided by the present invention can form a permanent and firm waterproof layer on the surface and inside of the concrete, which has the functions of inhibiting water absorption and preventing Cl - , anti-ultraviolet performance and breathable effect, which can effectively improve the waterproof and anti-corrosion properties of concrete and extend the service life of concrete. DETAILED DESCRIPTION

[0034] The present invention is further described below by describing specific embodiments, but this is not a limitation of the present invention. Those skilled in the art can make various modifications or improvements based on the basic idea of ​​the present invention, but as long as they do not deviate from the basic idea of ​​the present invention, they are all within the scope of the present invention. The ingredients used in the present invention are all commercially available conventional products.

[0035] Example 1. Preparation of lithium silicate composite

[0036] a. Add β-cyclodextrin to deionized water, heat to 70°C and stir to dissolve to obtain a saturated β-cyclodextrin aqueous solution;

[0037] b. Add lithium silicate to deionized water and stir evenly, the volume ratio of lithium silicate to deionized water is 1:1 to obtain a lithium silicate solution;

[0038] c. Slowly add the lithium silicate solution obtained in step b to the saturated β-cyclodextrin aqueous solution obtained in step a, wherein the volume ratio of the lithium silicate solution to the saturated β-cyclodextrin aqueous solution is 1:3, stir the reaction in a constant temperature water bath at 50°C for 4 hours, cool to room temperature, place at 4°C for 12 hours, filter, wash with water, and dry at 55°C for 10 hours to obtain.

[0039] Example 2. Preparation of isobutyltriethoxysilane emulsion

[0040] A. Add β-cyclodextrin into deionized water, heat to 70°C and stir to dissolve, to prepare a saturated β-cyclodextrin aqueous solution;

[0041] B. Place Span 80 and isobutyl triethoxysilane in a homogenizer and stir evenly, wherein the volume ratio of Span 80 to isobutyl triethoxysilane is 3:1, to obtain an oil phase;

[0042] C. Heat the saturated β-cyclodextrin aqueous solution obtained in step A to 45°C, then add the oil phase obtained in step B, the volume ratio of the oil phase to the β-cyclodextrin aqueous solution being 1:2, stir at a constant temperature of 45°C for 4 hours, and let stand to cool.

[0043] Example 3: A concrete sealing and curing agent

[0044] The concrete sealing and curing agent is composed of the following components and their weight parts:

[0045] 24 parts of lithium silicate complex, 16 parts of isobutyl triethoxy silane emulsion, 2 parts of penetrant, 2 parts of Tween 80 and 38 parts of deionized water; the lithium silicate complex is the lithium silicate complex prepared in Example 1, the isobutyl triethoxy silane emulsion is the isobutyl triethoxy silane emulsion prepared in Example 2, and the penetrant is polyethylene oxide with a molecular weight of 3000-5000.

[0046] Preparation method:

[0047] First, add the penetrant and Tween 80 into deionized water and stir evenly, then add the lithium silicate complex and isobutyl triethoxy silane emulsion and stir evenly to obtain the product.

[0048] Example 4: A concrete sealing and curing agent

[0049] The concrete sealing and curing agent is composed of the following components and their weight parts:

[0050] 26 parts of lithium silicate complex, 14 parts of isobutyl triethoxy silane emulsion, 2 parts of penetrant, 2 parts of Tween 80 and 40 parts of deionized water; the lithium silicate complex is the lithium silicate complex prepared in Example 1, the isobutyl triethoxy silane emulsion is the isobutyl triethoxy silane emulsion prepared in Example 2, and the penetrant is polyethylene oxide with a molecular weight of 3000-5000.

[0051] The preparation method is similar to that of Example 3.

[0052] Example 5: A concrete sealing and curing agent

[0053] The concrete sealing and curing agent is composed of the following components and their weight parts:

[0054] 28 parts of lithium silicate complex, 12 parts of isobutyl triethoxy silane emulsion, 2 parts of penetrant, 2 parts of Tween 80 and 42 parts of deionized water; the lithium silicate complex is the lithium silicate complex prepared in Example 1, the isobutyl triethoxy silane emulsion is the isobutyl triethoxy silane emulsion prepared in Example 2, and the penetrant is polyethylene oxide with a molecular weight of 3000-5000.

[0055] The preparation method is similar to that of Example 3.

[0056] Comparative Example 1: A concrete sealing and curing agent

[0057] The concrete sealing and curing agent is composed of the following components and their weight parts:

[0058] 26 parts of lithium silicate, 14 parts of isobutyl triethoxy silane emulsion, 2 parts of penetrant, 2 parts of Tween 80 and 40 parts of deionized water; the isobutyl triethoxy silane emulsion is the isobutyl triethoxy silane emulsion prepared in Example 2, and the penetrant is polyethylene oxide with a molecular weight of 3000-5000.

[0059] The preparation method is similar to that of Example 3.

[0060] The difference from Example 4 is that the lithium silicate is a commercially available product.

[0061] Comparative Example 2: A concrete sealing and curing agent

[0062] The concrete sealing and curing agent is composed of the following components and their weight parts:

[0063] 26 parts of lithium silicate complex, 14 parts of lithium methyl silicate, 2 parts of penetrant, 2 parts of Tween 80 and 40 parts of deionized water; the lithium silicate complex is the lithium silicate complex prepared in Example 1, and the penetrant is polyethylene oxide with a molecular weight of 3000-5000.

[0064] The preparation method is similar to that of Example 3.

[0065] The difference from Example 4 is that the isobutyltriethoxysilane emulsion is replaced by lithium methyl silicate.

[0066] Comparative Example 3: A concrete sealing and curing agent

[0067] The concrete sealing and curing agent is composed of the following components and their weight parts:

[0068] 26 parts of lithium silicate complex, 14 parts of isobutyl triethoxysilane emulsion, 2 parts of penetrant, 2 parts of Tween 80 and 40 parts of deionized water; the lithium silicate complex is the lithium silicate complex prepared in Example 1, and the penetrant is polyethylene oxide with a molecular weight of 3000-5000;

[0069] The preparation method of the isobutyl triethoxy silane emulsion is:

[0070] A. adding Peregal O into deionized water, and stirring evenly in a homogenizer, wherein the volume ratio of Peregal O to deionized water is 3:1, to obtain a water phase;

[0071] B. Place Span 80 and isobutyl triethoxysilane in a homogenizer and stir evenly, wherein the volume ratio of Span 80 to isobutyl triethoxysilane is 3:1, to obtain an oil phase;

[0072] C. Heat the aqueous phase in step A to 45°C, then add the oil phase prepared in step B, with the volume ratio of aqueous phase to oil phase being 1:1, stir at a constant temperature of 45°C for 4 hours, and let stand to cool.

[0073] The preparation method is similar to that of Example 3.

[0074] Test Example 1: Test on the permeability of concrete curing agent

[0075] 1. Test materials:

[0076] Concrete sealing and curing agents of Example 3, Example 4, Example 5, Comparative Example 1, Comparative Example 2 and Comparative Example 3.

[0077] 2. Test methods:

[0078] The concrete was made with reference to GB / T50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", the design strength of the base concrete was C30, and the specimen size was 200mm×200mm×200mm. The prepared concrete specimens were placed in a standard curing room for 28 days, and the concrete sealing and curing agents of Example 3, Example 4, Example 5, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were applied to the concrete specimens, and the penetration depth of the sealing and curing agent applied to the concrete was measured by the water spray color development method.

[0079] 3. Test results:

[0080] The test results are shown in Table 1.

[0081] Table 1 Penetration depth of sealing curing agent in concrete

[0082] Penetration depth (mm) Example 3 Group 16.8 Example 4 Group 18.4 Example 5 Group 16.5 Comparative Example 1 7.3 Comparative Example 2 12.6 Comparative Example 3 10.4

[0083] It can be seen from Table 1 that the concrete sealing and curing agent provided by the present invention has strong penetration performance, and the penetration depth in concrete with a strength of C30 is greater than 16.5 mm, which is more conducive to the sealing and curing agent to improve the compactness and waterproof and anti-corrosion effect of concrete.

[0084] Test Example 2: Concrete Performance Determination Test

[0085] 1. Test materials:

[0086] Concrete sealing and curing agents of Example 3, Example 4, Example 5, Comparative Example 1, Comparative Example 2 and Comparative Example 3.

[0087] 2. Test methods:

[0088] The concrete was made according to GB / T50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete". The design strength of the base concrete was C30, and the initial slump was controlled to be 140±20mm. The prepared concrete specimens were placed in a standard curing room for 28 days, and the concrete sealing and curing agents of Example 3, Example 4, Example 5, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were applied to the concrete specimens 3 times. The hardness and compressive strength were measured 28 days after the coating, and the base concrete was used as the control group. Among them:

[0089] 2.1. Concrete hardness test: Mohs hardness tester is used, the specimen size is 150mm×150mm×150mm, and a pair of molded sides are painted.

[0090] 2.2. Concrete compressive strength: Refer to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the specimen size is 100mm×100mm×100mm, and six surfaces are painted.

[0091] 3. Test results

[0092] The test results are shown in Table 2.

[0093] Table 2 Concrete hardness and compressive strength test data

[0094] Mohs hardness Compressive strength (MPa) Control group 5.5 40.5 Example 3 Group 9.5 45.5 Example 4 Group 9.5 46.3 Example 5 Group 9.5 45.0 Comparative Example 1 7.5 42.8 Comparative Example 2 8.5 43.4 Comparative Example 3 8.5 44.1

[0095] As shown in Table 2, after the concrete sealing and curing agent prepared in Examples 3 to 5 of the present invention is applied, the surface hardness of the concrete can reach 9.5, and the surface hardness of the concrete is increased by 4 compared with the control group; compared with the control group, the compressive strength of the concrete is increased by at least 11%. This indicates that the components of the concrete sealing and curing agent provided by the present invention interact with each other to enhance the surface hardness and compressive strength of the concrete.

[0096] Test Example 3: Concrete Waterproofing and Anticorrosion Test

[0097] 1. Test materials:

[0098] Concrete sealing and curing agents of Example 3, Example 4, Example 5, Comparative Example 1, Comparative Example 2 and Comparative Example 3.

[0099] 2. Test methods:

[0100] The concrete specimens were prepared by the method of Test Example 1, and the water penetration resistance, chloride ion penetration resistance and carbonization performance of the concrete specimens were measured, with the base concrete as the control group.

[0101] 2.1. Determination of concrete water penetration resistance: Refer to GB / T50082-2009J "Test method for long-term performance and durability of ordinary concrete" for determination. Use a truncated cone specimen with an upper diameter of 175mm, a lower diameter of 185mm, and a height of 150mm. Apply sealing and curing agent on the water-facing surface. When the initial water pressure is 0.2MPa, increase it by 0.1MPa every 8h until it reaches 1.0MP and maintain it for 8h. Split the specimen to measure the average water seepage height.

[0102] 2.2. Determination of concrete resistance to chloride ion penetration: The NEL method in CCES01-2004 "Guide to Durability Design and Construction of Concrete Structures" was used. The specimen size was Φ100×50mm and six surfaces were painted.

[0103] 2.3. Determination of concrete carbonization performance: refer to GB / T50082-2009J "Test method for long-term performance and durability of ordinary concrete" for determination. The specimen size is 40mm×40mm×160mm, and a pair of molded sides are painted as carbonization surfaces.

[0104] 3. Test results:

[0105] The test results are shown in Table 3.

[0106] Table 3 Concrete waterproof and anti-corrosion test data

[0107]

[0108] It can be seen from Table 3 that the water permeability resistance, chloride ion permeability resistance and carbonization resistance of the concrete coated with the concrete sealing and curing agent prepared in Examples 3 to 5 of the present invention are significantly improved, indicating that the concrete sealing and curing agent provided by the present invention can effectively improve the waterproof and anti-corrosion properties of concrete, and can effectively improve the durability of concrete.

Claims

1. A concrete sealing and curing agent, characterized in that: It includes the following ingredients and their weight parts: 20-30 parts of lithium silicate complex, 10-18 parts of isobutyl triethoxy silane emulsion, 1-3 parts of penetrant, 1-2 parts of Tween 80 and 35-45 parts of deionized water; The preparation method of the isobutyl triethoxy silane emulsion is: A. Add β-cyclodextrin to deionized water, heat to 65-70°C and stir to dissolve, to obtain a saturated β-cyclodextrin aqueous solution; B. Place Span 80 and isobutyltriethoxysilane in a homogenizer and stir evenly to obtain an oil phase; C. Heat the saturated β-cyclodextrin aqueous solution obtained in step A to 40-45° C., then add the oil phase obtained in step B, stir at a constant temperature for 3-4 hours, and let stand to cool. The preparation method of the lithium silicate composite is: a. Add β-cyclodextrin to deionized water, heat to 65~70℃ and stir to dissolve, to obtain a saturated β-cyclodextrin aqueous solution; b. Add lithium silicate to deionized water and stir evenly, the volume ratio of lithium silicate to deionized water is 1:1 to obtain a lithium silicate solution; c. Slowly add the lithium silicate solution obtained in step b to the saturated β-cyclodextrin aqueous solution obtained in step a, stir the reaction in a constant temperature water bath, cool to room temperature, place at 4°C for 12 to 24 hours, filter, wash with water, and dry at 50 to 55°C for 8 to 10 hours to obtain.

2. The concrete sealing and curing agent according to claim 1, characterized in that: It includes the following ingredients and their weight parts: 26 parts of lithium silicate complex, 14 parts of isobutyltriethoxysilane emulsion, 2 parts of penetrant, 2 parts of Tween 80 and 40 parts of deionized water.

3. The concrete sealing and curing agent according to claim 1, characterized in that: In step c, the volume ratio of the lithium silicate solution to the saturated β-cyclodextrin aqueous solution is 1:(2-3).

4. The concrete sealing and curing agent according to claim 1, characterized in that: The temperature of the constant temperature water bath in step c is 45-55° C., and the reaction time is 3-4 hours.

5. The concrete sealing and curing agent according to claim 1, characterized in that: In the step B, the volume ratio of Span 80 to isobutyltriethoxysilane is 3:

1.

6. The concrete sealing and curing agent according to claim 1, characterized in that: The volume ratio of the oil phase to the β-cyclodextrin aqueous solution is 1:

2.

7. The concrete sealing and curing agent according to claim 1 or 2, characterized in that: The penetrant is polyethylene oxide with a molecular weight of 3000-5000.

8. The method for preparing the concrete sealing and curing agent according to any one of claims 1 to 7, characterized in that: The following steps are involved: First, add the penetrant and Tween 80 into deionized water and stir evenly, then add the lithium silicate complex and isobutyl triethoxy silane emulsion and stir evenly to obtain the product.

Citation Information

Patent Citations

  • Improved liquid concrete seal curing agent

    CN102815885A

  • Concrete seal curing agent

    CN104150954A

  • Concrete curing agent and construction process thereof

    CN113185184A

  • Preparation method of highly-dispersed coated concrete expanding agent

    CN110372252A

  • Lithium silicate-based organic-inorganic composite concrete permeation protective agent

    CN115124275A